MBMQA: A Multicriteria-Aware Routing Approach for the IoT 5G Network Based on D2D Communication; Electronics; Vol. 10, iss. 23 - Tilwari V. Valmik; Hindia M. H. D. N. MHD Nour; Dimyati K. Kaharudin; Dzhayakodi (Jayakody) Arachshiladzh D. N. K. Dushanta Nalin Kumara; Solanki S. Sourabh; Sinha R. S. Rashmi Sharan; Hanafi E. Effariza (2021, 2021)
Title screen